Molecular level changes during suppression of Rhizoctonia solani growth by humic substances and relationships with chemical structure - Shiping Wei; Guilong Li; Pengfa Li; Cunpu Qiu; Chunyu Jiang; Ming Liu; Meng Wu; Zhongpei Li (Ecotoxicology and Environmental Safety, 2021)
Elucidation of the inhibitory effects of humic substances (HSs) on phytopathogenic fungi and the underlying molecular mechanisms are highly important for improved biocontrol. In this study, we investigated the growth suppression, morphological characteristics, transcriptomic sequence, and radical signals of Rhizoctonia solani following HS addition (50 mg/L). Through mycelial cultured experiment, mycelia growth of R. solani had been suppressed with HS addition, and the inhibition rate was 24.88 ± 0.11% compared to the control. Field emission-scanning electron microscopy showed increased and superimposed branching mycelial growth, with a shriveled appearance. RNA samples of R. solani cultured with or without HSs were both extracted to examine the sequence on molecular level by Illumina HiSeq sequencing platform. RNA sequencing analysis revealed 175 differentially expressed genes (DEGs; 111 upregulated and 64 downregulated) between the HSs treatment and control. The upregulated unigenes were annotated and significantly enriched to three molecular processes: vitamin B6 metabolism, ABC transporters, and glutathione metabolism, while the downregulated unigenes were annotated to carbohydrate metabolism, but not significantly enriched. Real time-quantitative polymerase chain reaction analysis showed that the unigenes related to hexokinase, glucose-6-phosphate isomerase, glutathione synthase, and glutathione reductase were significantly decreased (by 60.03%, 70.70%, 60.33%, and 57.59%, respectively), while those related to glutathione S-transferase were significantly increased (2.66-fold). The electron paramagnetic resonance spectra showed that HSs induced increased the intensity of radical signals of R. solani in a cultured system increased by 59.56% compared to CK (without HSs addition). Network analysis based on DEGs expression and the chemical structure of HSs revealed that the carbonyl moiety in HSs formed the most links with nodes of the DEGs (sum of the links of positive and negative effects = 70), implicating this structure as the active fraction responsible for the inhibitory effect. This study provides molecular and chemical evidence of the biofungicidal activity of HSs with the potential for practical application.